OPTIMIZATION AND ENERGY SAVING WHEN CHOOSING THE SITE OF INSTALLATION OF A CRUSHING STATION IN A MOUNTAINOUS TERRAIN CASE OF THE DJBEL EL BORDJ CAREER, SIDI BELABBAS, ALGERIA - RACHID KHEBBAB; SAMIR REMLI; ISSAM ROUAIGUIA; AISSA BENSELHOUB (Journal of Engineering Studies and Research)
In open pit or underground mines and quarries, especially in mountainous terrain, the choice of the perfect place to install a crushing station requires a decision finalized by a detailed study of the areas close to the quarries such as the water drainage, the morphology of the deposit, the installed capacity, the opening mode of the deposit etc. For this purpose, in this article we will propose an installation of the crushing station of the quarry Djbel El Bordj which serves to save energy throughout the life of the quarry, and also will gain the transportation distance of the stones that determines the number of dumpers needed for planned production.